Antibiotic resistance properties of Staphylococcus epidermidis isolated from hospitals in Selangor / Asmirah Ahmadunissah, Shafiq Aazmi and Aziyah Abdul-Aziz - Ahmadunissah, Asmirah; Aazmi, Shafiq; Abdul-Aziz, Aziyah (Faculty of Applied Sciences, 2021)
A total of 89 Coagulase-Negative Staphylococci (CoNS) samples used in this study were collected from clinical hospitals in Selangor. These isolates were grown on Mannitol Salt Agar (MSA) to screen for pink colonies that do not reduce mannitol which is a characteristic of CoNS. The purified isolates were subjected to standard biochemical tests which include Gram stain, slide coagulase, catalase, and urease test. Identification of Staphylococcus epidermidis was performed using the tuf gene sequencing method which confirmed the species at a total of 60 out of the 89 isolates. When tested against several antibiotics, 41.7% of the isolates were found to be resistant to cefoxitin followed by erythromycin (38.3 %), gentamicin (16.7 %), rifampin (16.7 %), clindamycin (15.0 %), and ciprofloxacin (8.3 %). In contrast, all of the S. epidermidis isolates were sensitive against linezolid. This supports the use of linezolid in the current treatment of S. epidermidis infections. Hence, the speciation of S. epidermidis and its antibiotic resistance patterns may further establish their role as a significant pathogen and help in initiating proper antimicrobial therapy.